The Role of Family Against Children's Anxiety After Disaster of Kelud Eruptions - Agus Khoirul Anam; Andi Hayyun Abiddin (Jurnal Keperawatan, 2022)
Introduction: Children are greatly affected by disasters and are more likely to be anxious than other groups of people. In a disaster, children experience simultaneous and ongoing disruptions in their families, schooling, health, friendship, and other critical areas of their lives. However, the role of the family is needed to prevent those problems. Objectives: The objective of this study was to describe the role of the family against children's anxiety children after the disaster of Kelud volcano. Methods: A cross-sectional study was used in this study. A purposive sampling method was used to determine families with children who have experienced anxiety in Sugih Waras village, Kediri, as the samples. The questionnaire on the family’s role and attitude towards children with anxiety was distributed to respondents, then analyzed descriptively - the result presented in the frequency and percentage. Results: Twenty-seven families were recruited in this study. The result showed that 81,5% of families have somewhat minor roles, and only 18,5% of families have promising roles in preventing the children’s anxiety after the Kelud volcano disaster. Conclusions: Most respondents related that the role in preventing children who experienced anxiety after the Kelud volcano disaster was still low. So, knowledge and understanding of the family role to prevent anxiety in children are necessary.